PERISTILAHAN DALAM PROSES NGUMA DAYAK BAKATI DUSUN SEMPAYUK, KECAMATAN LUMAR, KABUPATEN BENGKAYANG: KAJIAN SEMANTIK - Rahmad, Leo; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is focused on the semantic terminology in the process of the Dayak Bakati in Sempayuk, Lumar Subdistrict, Bengkayang Regency. Traditional rice farming is about processes, tools, and place names. The general problem which is the main subject of this research is Terminology in the Process of Nguma Dayak Bakati in Sempayuk Hamlet, Lumar Subdistrict, Bengkayang Regency which starts from the pratanam, planting and harvest stages using semantic studies. The specific problems of this study are as follows. Forms of terminology, lexical meanings and cultural meanings, and implementation of learning Indonesian. This study aims to analyze the forms of terminology, lexical meanings and cultural meanings, and the application of Indonesian language learning in terminology in the process of the Dayak Bakati. Based on the analysis, it was found that in the case of Dayak rice farming Bakati in Sempayuk Hamlet there were 40 data, 9 pre-harvest processes, 3 planting processes, 3 harvest processes, 20 tool names, and 5 place names. The lexical area contained in terminology in the process of the Dayak Bakati in Sempayuk, subdistrict Bengkayang covers the process of planting, planting, harvesting, tools, and place names. Keywords: Lexical Meaning, Terminology Nguma, Semantic Bakati